The impact of learner metacognition and goal orientation on problem-solving in a serious game environment. (January 2020) - Liu, Sa; Liu, Min
Abstract: To understand the impact of learner metacognition and goal orientation on problem-solving, this study investigated 159 undergraduate students' metacognition, goal orientations, and their problem-solving performances and processes in a laboratory setting using a Serious Game (SG) environment that adopts problem-based learning (PBL) pedagogy to teach space science. Utilizing cluster analysis, multiple regression, similarity measure and data visualization, this study analyzed multiple data sources, including computer log data, problem-solving performance scores, and survey data. The results show that both learner metacognition and goal orientation affected problem-solving. The findings of this study offer insights of how learner characteristics impact on problem-solving in SG environments with PBL pedagogy. It also contributes to understanding the design of SG environments to benefit learners based on their metacognitive levels. Highlights: Computer log data was used to analyze leaner problem-solving process. Similarity measure was used to analyze sequence pattern. Learner metacognition affected learner problem-solving in a serious game. Learner goal orientation affected learner problem-solving in a serious game. Dunning-Kruger effect and problem complexity could be the possible explanation forlearner problem-solving differences.